KURIKULUM CINTA SEBAGAI STRATEGI MODERASI BERAGAMA DALAM DUNIA PENDIDIKAN: TINJAUAN LITERATUR - Khairani, Vira; Fitriani, Fitriani; Ekowati, Endang; Daulay, Ilham Ramadhan; Darmawan, Diki; Anggraini, Vina; Aslami, Syafrida (Studia Sosia Religia, 2025)
Religious moderation is a religious approach that emphasizes moderation, tolerance, and respect for differences. In the world of education, this approach is important for shaping the character of students who are peaceful and inclusive. The Ministry of Religious Affairs of the Republic of Indonesia has responded to the challenges of intolerance and radicalism by introducing the idea of the Love Curriculum, an approach that integrates the values of love into the learning process. This curriculum is based on four main pillars: love for God, fellow human beings, the environment, and the homeland. Not as a new subject, the Love Curriculum is designed to incorporate values of love into all subjects and interactions within the educational environment. This article uses a literature review approach to educational policies, religious writings, and academic research findings to analyze how the Love Curriculum can serve as a preventive strategy against radicalism. The review results indicate that internalizing the value of love in the curriculum has the potential to create a peaceful school culture, strengthen national identity, and minimize religious exclusivity. However, implementing the Love Curriculum requires teacher readiness, adequate training, and support from a harmonious educational ecosystem. Thus, the Love Curriculum is an important innovation in strengthening religious moderation in Indonesian education.